Silicon-oriented regio- and enantioselective rhodium-catalyzed hydroformylation - Cai You (Nature Portfolio, 2018)
Hydroformylation of 1,2-disubstituted alkenes usually occurs at the α position of the directing heteroatom. Here, the authors report the asymmetric rhodium-catalyzed hydroformylation of 1,2-disubstituted alkenylsilanes with excellent regioselectivity at the β position (relative to the silicon heteroatom) and enantioselectivity.